Strategic Analysis for the Grain Grinders' establishments in Baghdad governorate and problems suffered by the industry, along with the possibility to predict its products - زينب عبد الزهرة جعفر أ.م.د. ناهض هاتف محمد (College of Education for Women, 2019)
Geography of industry has been considered a branch of important economic geographical branches. This importance has been regarded as a reflection on the industrial sector contribution in economies of any state since they contribute into the total national product ; it also assimilates a huge number of labor hands . The industry of grains grinding has been considered as one of the main food industries having a main role in satisfying the need of the population from the foods. The industry is continued to use the food as daily meal . Here, it should predict the population in Baghdad and for every district until the end of 2025 and knowing either these grains grinders are able to meet and satisfy the needs of populations of flours, making strategic analysis focusing on the weak and strong points.